A Novel Laser-Based Display and Imaging Combined System - Xiaohui Ma; Anting Wang; Zhe Cui; Fenghua Ma; Hai Ming (IEEE Photonics Journal, 2018)
Laser-based displays can offer a wide color gamut to the viewers due to the narrow bandwidth of laser source, which is quite different from traditional display systems. Therefore, the color rendition standards for traditional displays are no longer suitable for laser-based displays. An optimized and practical color reproduction system is proposed and demonstrated for laser-based displays in this paper. Not only the three primary wavelengths are well chosen by considering the luminance efficiency, color gamut, and color matching function, but also the response function of a camera system is optimized for a simplified color reproduction procedure. A remarkably high color rendition quality is presented in our experiment compared with traditional displays.